2009
DOI: 10.3171/2009.2.jns081380
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting postoperative cerebrospinal fluid leaks after retrosigmoidal craniotomy for vestibular schwannomas

Abstract: Surgery for recurrent tumors is a significant risk factor for the development of CSF leaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 40 publications
3
29
3
Order By: Relevance
“…2,3,5,7,9,25,26,28 We found that the CSF leakage rate was higher in older patients, in those with a longer duration of symptoms, those with polycyclic VSs, those with tumors that had an inhomogeneous internal structure, and in cases of severe hydrocephalus. A slower VS growth rate, frequently observed in the elderly patients, could possibly increase the period of exposure to the VS-related elevated protein level, thereby leading to irreversible alterations in CSF circulation and resorption.…”
Section: Predictive Factors For Csf Leaksmentioning
confidence: 65%
“…2,3,5,7,9,25,26,28 We found that the CSF leakage rate was higher in older patients, in those with a longer duration of symptoms, those with polycyclic VSs, those with tumors that had an inhomogeneous internal structure, and in cases of severe hydrocephalus. A slower VS growth rate, frequently observed in the elderly patients, could possibly increase the period of exposure to the VS-related elevated protein level, thereby leading to irreversible alterations in CSF circulation and resorption.…”
Section: Predictive Factors For Csf Leaksmentioning
confidence: 65%
“…Whereas factors such as age, sex, and tumor size did not correlate with the occurrence of a CSF leak in our series, other studies have reported these factors to be significant. 4,5,11,20 These factors, among others, are fixed variables and, therefore, even if believed to influence the likelihood of a postoperative CSF leak, can only be used to counsel patients with regard to their risk of this complication. The fixed nature of these variables prevents either the surgeon or the patient from altering their effect.…”
Section: Discussion Elevated Bmi As a Risk Factor For A Csf Leakmentioning
confidence: 99%
“…A large mono-institutional experience has recently reported an 11% of incidence of postoperative CSF leaks among those patients in the neurosurgical population who are characterised by a high risk for developing postoperative fistulas. 2 In our experience before using TPD high risk patients (p-fossa surgery, revision surgery, BCNU wafers implant, old patients) presented a CSF leak incidence around 5%. A CSF fistula can actually occur with dural closure at risk.…”
Section: Discussionmentioning
confidence: 97%